2021
DOI: 10.3389/fimmu.2021.722451
|View full text |Cite
|
Sign up to set email alerts
|

L2pB1 Cells Contribute to Tumor Growth Inhibition

Abstract: Natural IgM (nIgM) antibodies play critical roles in cancer immunosurveillance. However, the role of B-1 B cells, the lymphocytes that produce nIgM, remains to be elucidated. L2pB1 cells, a subpopulation of B-1 B cells, have a unique poly-self-reactive nIgM repertoire and are capable of phagocytosis, potent antigen presentation, and immunomodulation. Using an inducible knock-in and knockout mouse model, we investigated the effect of the loss of L2pB1 cells in a B16F10 melanoma model. Our results show active tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…NAbs play a fundamental role in the defense against infectious pathogens ( 24 26 ) and in the elimination of noxious structures like dead cells and oxidized epitopes ( 27 , 28 ). Some NAbs are also able to eliminate tumor cells ( 19 , 20 , 29 ), pointing to a relevant role for these immunoglobulins and the B-1 cells secreting them in the defense against malignant transformations. Neu5GcGM3 ganglioside is not only overexpressed in several human tumors, but is also relevant for tumor biology ( 30 ) and exerts an immunosuppressive effect that promotes tumor growth ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAbs play a fundamental role in the defense against infectious pathogens ( 24 26 ) and in the elimination of noxious structures like dead cells and oxidized epitopes ( 27 , 28 ). Some NAbs are also able to eliminate tumor cells ( 19 , 20 , 29 ), pointing to a relevant role for these immunoglobulins and the B-1 cells secreting them in the defense against malignant transformations. Neu5GcGM3 ganglioside is not only overexpressed in several human tumors, but is also relevant for tumor biology ( 30 ) and exerts an immunosuppressive effect that promotes tumor growth ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A group of recent reports described a protective role for natural, tumor-reactive IgM secreted by B-1a cells in a mouse model of peritoneal carcinomatosis (17,18). Also, monoclonal IgM antibodies derived from B-1 cells expressing PD-L2 bind and induce cell death of a colon cancer cell line (19). Rawat et al suggested that NAbs play an important role in the elimination of neoantigen-expressing cells, and consequently in anti-tumor immunity (20).…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that B-1 cells expressing PD-L1 and PD-L2 can suppress T cells in response to cognate allostimulation ( 125 ). However, in tumor models, PD-L2-positive B-1 cells seem to play an anti-tumoral role rather than an immunosuppressive function ( 74 ). This effect will be further discussed in the following section.…”
Section: The Pro-tumor Activity Of B-1 Cellsmentioning
confidence: 99%
“…L2pB1 cells actively accumulate within MB16F10 melanoma tumors and their depletion promotes tumor growth and angiogenesis. Moreover, L2pB1 cells secrete IgM antibodies that can bind to both B16F10 melanoma cells and MC38 colon cancer tumor spheroids, leading to tumor apoptosis ( 74 ). The involvement of L2pB1 cells in cancer immunosurveillance may have broader implications beyond the production of tumor-reactive natural IgM alone.…”
Section: The Anti-tumor Function Of B-1 Cellsmentioning
confidence: 99%
“…B cells are the second adaptive immune cell population found in TME ( 194 , 195 ). B cells have been known to be carcinogenic for decades, but recent studies have linked their presence to improved prognosis in patients with cancer ( 196 ).…”
Section: Roles Of Exosomes In the Tmementioning
confidence: 99%